2020
DOI: 10.24191/ji.v15i2.311
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Intelligence Practices and Organizational Performance Linkage: A Review

Abstract: Scholars have intensely researched competitive Intelligence or CI for decades. This topic has been under constant investigation and development concerning business strategy in soaring business performance. This paper critically examines and integrates the Competitive Intelligence Practices by different industries and its relationship on organizational performances.  The review employed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and utilizes three databases (Science Direct, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The overall mean score of 3.572 indicates that 71.44% of the respondents agreed that moderate leadership levels impact CIE. This result shows that the respondents perceived CI use at various levels throughout the organisation's value chain and departments, regardless of position (Asri & Mohsin, 2020).…”
Section: Leadershipmentioning
confidence: 81%
See 4 more Smart Citations
“…The overall mean score of 3.572 indicates that 71.44% of the respondents agreed that moderate leadership levels impact CIE. This result shows that the respondents perceived CI use at various levels throughout the organisation's value chain and departments, regardless of position (Asri & Mohsin, 2020).…”
Section: Leadershipmentioning
confidence: 81%
“…Mohsin et al (2015) also found that CI positively correlated to innovative performance. In contrast, Asri and Mohsin's (2020) study deduced a relationship between CI practices and organisational performance. Magasa, Mphahlele and Awosejo (2014), and Stefanikova et al (2015) found that implementing and utilising CI enhance performance and affect an organisation's sustainable growth.…”
Section: Competitive Intelligence Embeddedness Customer Satisfaction ...mentioning
confidence: 88%
See 3 more Smart Citations